2013
DOI: 10.1002/hbm.22400
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in effective connectivity associated with relational reasoning

Abstract: Rostrolateral prefrontal cortex (RLPFC) is part of a frontoparietal network of regions involved in relational reasoning, the mental process of working with relationships between multiple mental representations. RLPFC has shown functional and structural changes with age, with increasing specificity of left RLPFC activation for relational integration during development. Here, we used dynamic causal modelling (DCM) to investigate changes in effective connectivity during a relational reasoning task through the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 74 publications
(167 reference statements)
2
19
0
Order By: Relevance
“…Nevertheless, structural MRI and activation studies have suggested that many of the regions assessed in our network analyses undergo developmental changes through adolescence [Gogtay et al, ; Luna et al, ; Rubia et al, ; Yurgelun‐Todd, ]. Changes in effective connectivity from adolescence to adulthood have been demonstrated in complex domains including reasoning [Bazargani et al, ] and processes related to language [Booth et al, ]. Other investigations in more fundamental domains such as reward processing, have provided negative results [Cho et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, structural MRI and activation studies have suggested that many of the regions assessed in our network analyses undergo developmental changes through adolescence [Gogtay et al, ; Luna et al, ; Rubia et al, ; Yurgelun‐Todd, ]. Changes in effective connectivity from adolescence to adulthood have been demonstrated in complex domains including reasoning [Bazargani et al, ] and processes related to language [Booth et al, ]. Other investigations in more fundamental domains such as reward processing, have provided negative results [Cho et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Of greatest relevance to the present review, a study focusing on the neurodevelopment of second-order relational reasoning recently showed that frontoparietal connections strengthened with age, and were more tightly coupled than shorter-range frontoinsular connections for second- relative to first-order relational problems (Bazargani et al, 2014). More broadly, various studies have shown that tighter resting-state functional connectivity among LFPN regions is associated with better relational reasoning, as measured by nonverbal IQ scores (Langeslag et al, 2013) or full-scale IQ scores (Song et al, 2008; Li and Tian, 2014).…”
Section: Lfpn Functional Connectivitymentioning
confidence: 93%
“…This result is also in agreement with previous findings from different approaches such as morphometry [Aichelburg et al, 2014;Krawczyk et al, 2010], and developmental studies in children. The latter studies suggested that maturation of the PFC and especially of the rlPFC is critical for relational reasoning in matrix problems [Crone et al, 2009], for semantic analogies [Wright et al, 2008], and visuospatial analogies [Bazargani et al, 2014;Thibaut et al, 2010;Wendelken et al, 2011]. These studies showed functional and structural changes in the left rlPFC during development, with decreasing grey matter volume and increasing specificity of left rlPFC activation for relational integration [for a review, see Dumontheil, 2014].…”
Section: The Left Rlpfc Is a Reliable Domain-general Region For Analomentioning
confidence: 99%